The Redox State Regulates RNA Degradation in the Chloroplast of Chlamydomonas reinhardtii - Salvador, Maria L. (American Society of Plant Physiologists, 1999)
A Chlamydomonas reinhardtii chloroplast transformant, designated MU7, carrying a chimeric (rbcL promoter: β-glucuronidase [GUS]: psaB 3′ end) gene whose transcripts have been found previously to be unstable in light (half-life of 20 min in light as opposed to a half-life of 5 h in the dark), was used to study the role of electron transport and of the redox state in the degradation of chloroplast transcripts in the light. Blocking photosynthetic electron transport with 3-(3,4-dichlorophenyl)-1,1-dimethylurea (DCMU) prevented the light-dependent breakdown of the pool of GUS transcripts in MU7 cells. Diamide, an oxidizing agent, caused a measurable delay in the degradation of GUS transcripts in the light. The addition of dithiothreitol (DTT), a dithiol reductant, to MU7 cells in which GUS transcript levels were stabilized by DCMU induced degradation of GUS transcripts. Similarly, DTT induced a decrease in the levels of GUS transcripts when added to MU7 cells in the dark period of the light/dark cycle, a period in which GUS transcript levels normally increase. The levels of transcripts of endogenous chloroplast genes were affected by DCMU and DTT in the same direction as levels of GUS transcripts. The results suggest a regulatory role of the redox state in the degradation of chloroplast transcripts in C. reinhardtii.